Abnormal Lipid Profile in Fast-Growing Broilers With Spontaneous Femoral Head Necrosis - Fan, Rubin; Liu, Kangping; Zhou, Zhenlei (Frontiers in Physiology, 2021)
This study investigated lipid metabolism in broilers with spontaneous femoral head necrosis (FHN) by determining the levels of markers of the blood biochemistry and bone metabolism. The birds were divided into a normal group and FHN group according to the femoral head scores of 3-, 4-, and 5-week-old chickens with FHN, and a comparative study was conducted. The study showed that spontaneous FHN broilers had a lipid metabolism disorder, hyperlipidemia, and an accumulation of lipid droplets in the femur. In addition, there were significant changes in the bone parameters and blood bone biochemistry markers, and the expression of genes related to lipid metabolism in the femoral head was also significantly increased. Therefore, FHN may result from dyslipidemia, which affects the bone growth and development of broilers.